2019
DOI: 10.2147/ijn.s226790
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparative Effect Of Curcumin Versus Liposomal Curcumin On Systemic Pro-Inflammatory Cytokines Profile, MCP-1 And RANTES In Experimental Diabetes Mellitus</p>

Abstract: PurposeAnti-inflammatory proprieties of curcumin were proved to be useful in various diseases, including diabetes mellitus. The aim of this study was to assess the anti-inflammatory comparative effect of curcumin solution with liposomal curcumin formula, regarding the improvement of serum levels of TNF-α (tumor necrosis factor-alpha), IL-6 (interleukin), IL-1α, IL-1β, MCP-1 (monocyte chemoattractant protein-1) and RANTES in experimental diabetes, induced by streptozotocin (STZ), in rats.Materials and methodsSi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 90 publications
3
30
0
Order By: Relevance
“…Furthermore, in this study liposomes were used as nanocarriers, owing to its enhanced stability, bioavailability, and shelf life for sensitive ingredients as they are assembled from phospholipid bilayers similar to cell membranes and their biphasic character making them suitable for being carriers for both hydrophilic (in the central aqueous compartment) and hydrophobic (in lipid bilayers) compound. 26,27 Tuftsin a tetrapeptide (Thr-Lys-Pro-Arg) stimulates immunomodulatory effects by binding specifically to macrophages, monocytes, and polymorphonuclear leukocytes (PMN). 28 Many studies have reported the anti-tumor efficacy of tuftsin in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study liposomes were used as nanocarriers, owing to its enhanced stability, bioavailability, and shelf life for sensitive ingredients as they are assembled from phospholipid bilayers similar to cell membranes and their biphasic character making them suitable for being carriers for both hydrophilic (in the central aqueous compartment) and hydrophobic (in lipid bilayers) compound. 26,27 Tuftsin a tetrapeptide (Thr-Lys-Pro-Arg) stimulates immunomodulatory effects by binding specifically to macrophages, monocytes, and polymorphonuclear leukocytes (PMN). 28 Many studies have reported the anti-tumor efficacy of tuftsin in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Each medication was dissolved in saline solution (0.9% sodium chloride) and the volume administrated i.p. was 1 mL [19]. The following doses were used: STZ-60 mg/100 g body weight (b.w.)…”
Section: Experimental Modelmentioning
confidence: 99%
“…One of the most used experimental models for testing various therapies addressing type 1 DM is based on STZ administration. STZ induces type 1 DM, with destruction of pancreatic beta cells and associated insulin deficiency, as a result of its cytotoxic effect, mediated by increased synthesis of reactive oxygen species (ROS) and subsequent inflammation [18][19][20]. A protective effect of EGCG on pancreatic beta cells has been already demonstrated in experimental studies [21]; meanwhile, oral chronic administration of EGCG proved to have hypoglycemic and hypolipidemic effects and to reduce oxidative stress in streptozotocin-diabetic rats [22].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that oral administration of curcumin inhibited edema induced by carrageenan at doses of 50–200 mg/kg in mice [ 6 ]. Moreover, curcumin has demonstrated beneficial effects in various diseases associated with inflammation, such as diabetes mellitus [ 7 ], myocardial infarction [ 8 ], and migraine [ 9 ]. While curcumin has many advantageous pharmacological properties, its development as a therapeutic agent is limited on account of its low aqueous solubility, poor absorption, and metabolic instability, which lead to poor oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%